Exposure to multiple metals and the risk of dyslexia - A case control study in Shantou, China. (15th August 2022) - Huang, Anyan; Zhang, Jingbing; Wu, Kusheng; Liu, Caixia; Huang, Qingjun; Zhang, Xuanzhi; Lin, Xuecong; Huang, Yanhong
Abstract: Environmental heavy metal exposure has been considered to be the risk factor for neurodevelopmental disorders in children. However, the available data on the associations between multiple metals exposure and the risk of dyslexia in China are limited. The purpose of our study was to examine the associations between urinary metal concentrations and Chinese dyslexia risk. A total of 56 Chinese dyslexics and 60 typically developing children were recruited. The urinary concentration of 13 metals were measured by inductively coupled plasma-mass spectrometer (ICP-MS). Binary logistic regression and the Probit extension of Bayesian kernel machine regression (BKMR-P) were used to explore the associations between multiple metal exposure and the risk of Chinese dyslexia. Our results indicated that Co, Zn and Pb were significantly associated with Chinese dyslexia in the multiple-metal exposure model. After adjusting the covariates, a positive association was observed between Pb and the risk of Chinese dyslexia, with the odds ratio (OR) in the highest quartiles of 6.81 (95%CI: 1.07–43.19; p –trend = 0.024). Co and Zn were negatively associated with the risk of Chinese dyslexia. Compared to the lowest quartile, the ORs of Co and Zn in the highest quartile are 0.13 (95%CI: 0.02–0.72; p –trend = 0.026) and 0.18 (95%CI: 0.04–0.88; p –trend = 0.038), respectively. In addition, BKMR-P analysis indicated that with the cumulative level across Co, Zn and Pb increased, the risk of Chinese dyslexia gradually declined and then rebounded, albeit non-significantly, and Pb was the major contributor in this association. In general, the urinary concentrations of Co, Zn and Pb were significantly associated with Chinese dyslexia. More prospective studies are needed to confirm the health effects of multiple metals exposure in children with Chinese dyslexia. Graphical abstract: Image 1 Highlights: The associations between 13 urinary metals concentrations and dyslexia in China. Pb showed a positive association with the risk of Chinese dyslexia. Co and Zn showed protective effects on Chinese dyslexia. The estimate values of overall effect and interaction of metals using Bayesian kernel machine regression.